Long-Term Safety and Efficacy of Subcutaneously Administered Tocilizumab for Adult Rheumatoid Arthritis: A Multicenter Phase 3b Long-term Extension Study. Issue 2 (December 2016) - Kivitz, Alan; Wallace, Thomas; Olech, Ewa; Borofsky, Michael; Devenport, Jenny; Pei, Jinglan; Michalska, Margaret
Abstract Introduction To assess the long-term safety and efficacy of subcutaneous tocilizumab (TCZ-SC) in US patients with rheumatoid arthritis (RA) who rolled over from the two global phase 3 studies, SUMMACTA (NCT01194414) and BREVACTA (NCT1232569), into this open-label, single-arm, phase 3b study. Methods Patients continued to receive TCZ-SC 162 mg weekly or every other week or switched from intravenous TCZ to TCZ-SC 162 mg qw for up to 84 weeks. The primary endpoint was the proportion of patients with serious adverse events (SAEs). Secondary endpoints included clinical efficacy, laboratory abnormalities, and immunogenicity. Results Of the 217 patients treated, 76.5% were female, and the mean age was 58.4 years. A total of 23 patients (10.6%) had ≥1 SAE. The most common SAEs were infections (3.7%). Alanine aminotransferase elevations (38.2%) were not associated with hepatic injury. Grade 3/4 neutropenia (3%) was transient and not associated with serious infections. Immunogenicity was low (<1%) and not associated with SAEs. No anaphylaxis or deaths occurred. Thirteen patients (6.0%) withdrew due to safety reasons. Mean Clinical Disease Activity Index and Disease Activity Score in 28 joints remained stable throughout the trial. Conclusions The long-term safety of TCZ-SC during the long-term extension period was consistent with the safety profiles from SUMMACTA and BREVACTA, with no new safety signals. Efficacy improvements observed from baseline remained stable over time. These results demonstrated the durability of the safety and efficacy responses, and low immunogenicity, with long-term exposure to TCZ-SC in patients with RA. Funding : F. Hoffmann-La Roche, Ltd. Trial registration number : ClinicalTrials.gov identifier, NCT01662063.